PENGARUH SUPERVISI KLINIS DAN PENGAWASAN TERHADAP KINERJA GURU DI SMA NEGERI 1 KECAMATAN SEMENDE DARAT ULU KABUPATEN MUARA ENIM - Handayani, Reska; Ahyani, Nur; Nurlina, Nurlina (Jurnal Manajemen Pendidikan, 2024)
The objectives of this research: 1) To determine the effect of clinical supervision on the performance of teachers at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency; 2) To determine the effect of supervision on the performance of teachers at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency; 3) To determine the effect of clinical supervision and supervision on the performance of teachers at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency. This research was carried out at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency with a total research sample of 57 teachers. Data collection techniques were carried out through observation, documentation studies and distributing questionnaires. The results of this research are: 1) There is a partially significant influence between clinical supervision on the performance of teachers at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency, where the calculated t value is greater than t table (3.274 > 1.671); 2) There is a partially significant influence between supervision on the work performance of teachers at SMA Negeri 1 Semende Darat Ulu, Semende Darat Ulu District, Muara Enim Regency where the calculated t value is greater than t table (3.127 > 1.671).